1999
DOI: 10.1006/jeem.1999.1092
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Monitoring and Enforcement of a Transferable Emissions Permit System

Abstract: The literature on noncompliant firms in transferable emissions permit systems offers little guidance to policymakers that must determine how to commit resources to monitor firms and punish violations in such systems. We consider how a budget-constrained enforcement autl1ority that seeks to minimize aggregate noncompliance in a transferable emissions permit system should allocate its monitoring and enforcement efforts among heterogeneous firms. With a conventional model of firm behavior in a transferable permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 11 publications
4
100
0
2
Order By: Relevance
“…As in Strandlund and Dhanda (1999) and Chavez and Salgado (2005), we assume that the penalty function, f ðtÞ is zero for zero quota violation, t ¼ hðeÞ À q ¼ 0, and strictly increasing and convex for a positive quota violation, t ¼ hðeÞ À q [ 0. We assume as Chavez et al (2008) that f ðtÞ ¼ a 2 À Á t 2 þ ct; with and c greater than zero.…”
Section: A Simple Fishery With Illegal Fishingmentioning
confidence: 99%
See 1 more Smart Citation
“…As in Strandlund and Dhanda (1999) and Chavez and Salgado (2005), we assume that the penalty function, f ðtÞ is zero for zero quota violation, t ¼ hðeÞ À q ¼ 0, and strictly increasing and convex for a positive quota violation, t ¼ hðeÞ À q [ 0. We assume as Chavez et al (2008) that f ðtÞ ¼ a 2 À Á t 2 þ ct; with and c greater than zero.…”
Section: A Simple Fishery With Illegal Fishingmentioning
confidence: 99%
“…We assume that the enforcement authority cannot commit on the initial quotas recommended by scientific committees. We build upon Strandlund and Dhanda (1999), Chavez and Salgado (2005), and Chavez et al (2008) to analyze the enforcement authority behavior in a simple game theoretic model where the fisherman level of quota violation, non-compliance, is endogenous. As Strandlund and Dhanda (1999) quota violation is induced by an enforcement technology which is insufficient to guarantee full compliance.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, I present a basic model of enforcement of incentive-based environmental policy that has been used extensively in the prior literature (e.g., Harford, 1978;Stranlund and Dhanda, 1999;Stranlund et al 2002). The model yields one simple insight that I rely on to analyze practical enforcement issues in the rest of the chapter.…”
Section: Incentives For Compliance With a Climate Policymentioning
confidence: 99%
“…Within the context of designing market-based pollution control policies, several authors have provided theoretical analyses of compliance incentives, the consequences of noncompliance, and the design of enforcement strategies (e.g., Keeler 1991, Malik 1990, 1992, vanEgteren and Weber 1996, Stranlund and Dhanda 1999, Stranlund and Chavez 2000, Chavez and Stranlund 2003, Stranlund, Costello and Chavez 2005. Taken as a whole, this literature suggests that firms' incentives toward noncompliance under market-based regulations, as well as the design of enforcement strategies to counteract these incentives, are quite different from compliance and enforcement of other policy instruments, particularly command-andcontrol regulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, Stranlund and Dhanda (1999) have shown that the individual compliance choices of risk neutral competitive firms in emissions trading programs are independent of differences in any firm-level characteristic. Consequently, regulators have no reason to condition their enforcement effort on firm-level characteristics.…”
Section: Introductionmentioning
confidence: 99%